Analisis Tindak Tutur Representatif dalam Daftar Putar "Alam Semesta dan Luar Angkasa" pada Kanal YouTube Kok Bisa? - Arsya Ramadhani; Dini Sustiani; Ikhwatika Putri Hardiansah; Kalista Fitri Maharani; Nazhifa Destrianti Farradina; Asep Purwo Yudi Utomo; Didi Pramono; Kodrat Eko Putro Setiawan (Jurnal Kajian dan Penelitian Umum, 2025)
In language, there are various types of speech acts, one of which is representative speech acts. Each speech act has different purposes and objectives, depending on the context and situation. This research in pragmatics focuses on the intent or purpose found in the language we use daily, both in spoken and written forms. Spoken language is typically reflected in speech or utterances. One example of spoken language can be found on the YouTube channel "Kok Bisa?" particularly in the playlist titled “Alam Semesta dan Luar Angkasa.” This playlist piqued the author's interest and led to a systematic research study. The research employs a descriptive qualitative approach, with data collection techniques including free listening and note-taking. The analysis method used is the commensurate method, while the results are presented informally. This study focuses on representative speech acts such as stating, telling, complaining, suggesting, demanding, reporting, explaining, giving, showing, mentioning, and speculating. The data consists of all speech acts in the videos that contain representative speech acts. These are analyzed to understand how scientific meaning is conveyed in an informative and engaging manner. The results indicate that speech acts like stating and explaining are most frequently used to make complex scientific concepts more accessible. This research demonstrates that conveying information through social media, particularly YouTube, can effectively explain intricate science topics, thereby enhancing public interest and understanding of science.